DEVELOPMENT OF VIRTUAL LABORATORY FOR SIMPLE HARMONIC MOTION USING GEOGEBRA WITH BELAJAR ID ACCOUNT FOR SENIOR HIGH SCHOOL STUDENTS - Julaeha, Juju
The existence of laboratories in physics learning is essential. However, the reality is not all schools have adequate practicum tools. So alternative learning media are needed that can facilitate practicum activities. One of the innovations that can be done is to develop learning media in the form of virtual laboratories. The virtual laboratory developed should be able to facilitate practicum activities as well as a practicum in a physical laboratory. Students are facilitated to observe, collect data, process data, analyze data, and make conclusions from practicums that have been carried out. Therefore, the main purpose of this research is to develop a virtual laboratory that can help students carry out practicum activities virtually to increase students' understanding of the concepts they learn. This research uses the Research and Development (R&D) method with a 4D development model (Define, Design, Develop, Disseminate) which produces products in the form of virtual laboratory applications. Through curriculum analysis in high school, information was obtained that one of the materials that requires practicum activities is simple harmonic motion. GeoGebra software is predicted to be suitable for constructing virtual laboratories of simple harmonic motion because GeoGebra provides powerful visualization tools to depict graphs and simulate objects precisely according to given mathematical equations. Furthermore, to facilitate user access, a virtual laboratory application is embedded into a website built using belajar id account (Google Sites). The validation results showed that the average material expert assessment was 3.9 (very good criteria) and the average media expert assessment was 3.8 (very good criteria). The results of the response analysis showed that students and teachers "supported" the development of virtual labs. Therefore, based on the validation of media experts, material experts, and teacher and student responses, the virtual laboratory is suitable to be used as a practicum learning medium on simple harmonic motion material.